Ambiente, saúde e qualidade de vida : condições e perspectivas nos conjuntos habitacionais de Porto Rico, Estado do Paraná, Brasil. - Silva, Doris Marli Petry Paulo da (2009)
As part of the activities of the Doctorate Program in Ecology of Continental Aquatic Environments at the Maringa University State, a research project was conducted on the perception of quality of life by a segment of the residents of the municipality Porto Rico, Parana State, Brazil. The study investigated how environmental processes are related with the health conditions of the Porto Rico population and with their evaluations of their own quality of life; based on that knowledge, it would be possible to devise proposals to minimize such conditions. The study was conducted at the Flamingo, Por do Sol and Casa Feliz housing complexes, which are located in the urban area of town, during the months of June 2005 and January 2006. The sample consisted of 63 residents of all three complexes. Data were obtained through home surveys, using two forms devised by the World Health Organization's Group for Quality of Life (OMS, 1998): the Abbreviated Instrument for Quality of Life Assessment (WHOQOL-bref) and the Respondent Data Sheet, with additional data on the family members of that household. The data were processed using Statistical Analysis Software (SAS) and Statistical Package for the Social Sciences (SPSS) software, and the CHAID algorithm. Initially, the study evaluated the socioeconomic and work conditions of 63 families living in the aforementioned housing complexes, with a total of 224 people. Next, self-reported morbidity was compared between both groups of interviewees, and the CHAID technique was applied to explain the trends in the variables that explained the evaluation of the quality of life of that population, as analyzed by WHOQOL-bref. The results indicated that the social conditions of these families were influenced by their low levels of education, allied with the lack of work options, thus compromising family income. Residents of group B mentioned better health and income conditions. The findings of self-reported morbidity followed the national trend of acute infectious diseases caused by inadequate environmental conditions and of chronic illnesses, in groups of middle-aged and elderly groups, as results of chosen lifestyles and the social conditions of the residents. Most interviewees expressed satisfaction regarding their quality of life. The variables that generated the most dissatisfaction were related to pain and available transportation. The use of CHAID made possible the mapping of variables that interfered in the evaluations of each of the domains that make up the concept of 'quality of life', and its use is recommended in similar studies. It can be affirmed that a good quality of life is reflected, most of all, in individual quality of health, which confirms that quality of life depends on conditions of health and surroundings.